2008
DOI: 10.1002/anie.200705113
|View full text |Cite
|
Sign up to set email alerts
|

The Versatile Chemistry and Noncentrosymmetric Crystal Structures of Salt‐Inclusion Vanadate Hybrids

Abstract: Hybrid solids containing chemically dissimilar components have attracted much interest in advanced materials synthesis due to their structural versatility and multifunctional properties. Metal-organic frameworks (MOFs), for instance, have been extensively explored for their potential applications in technologically important fields such as heterogeneous catalysis, gas storage, and sensors. [1][2][3] These solids are moleculebased composite materials that contain metal ions or metal ion clusters as nodes and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Since vanadium can exist in several oxidation states and different coordination geometries a great number of structure types among metal vandates were discovered. Furthermore, metal vanadates can form non-centrosymmetric structures that may show some important properties, such as non-linear optical effects, piezoelectricity, ferroelectricity, and pyroeletricity [1]. A variety of polyoxovanadates have been synthesized under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since vanadium can exist in several oxidation states and different coordination geometries a great number of structure types among metal vandates were discovered. Furthermore, metal vanadates can form non-centrosymmetric structures that may show some important properties, such as non-linear optical effects, piezoelectricity, ferroelectricity, and pyroeletricity [1]. A variety of polyoxovanadates have been synthesized under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The four halogen atoms from the Ln(4)O 4 X 4 antiprisms also belong to the MX 8 cubes. The interplay between the {MLn 11 (Fig. 2, d) [17][18][19][20], the LnO 4 X 4 antiprisms never stack in "eclipsed", only in "staggered" motif.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach has been developed for the pure inorganics, which is based on the so-called "saltinclusion solids". These marry two chemically dissimilar constituents, which are usually the covalent and ionic sub-frameworks, in one structure [8][9][10][11][12]. In fact, these "salt inclusions" often act as templates for pores, channels, or interlayer spaces of the covalent framework.…”
Section: Introductionmentioning
confidence: 99%
“…Another novel strategy for synthesising and designing NCS materials has been described by Hwu et al [80][81][82][83] He has focused on salt-inclusion solids whose framework consists of mixed ionic and covalent sub-lattices. Hwu et al have utilised a combination of acentric polyanions, such as those found in silicates, along with first-order Jahn-Teller cations and chlorinecentred, acentric secondary building units (SBUs).…”
Section: Salt-inclusion Solidsmentioning
confidence: 99%